Triple Burden of Neurocognitive Impairment and Co-occurring Depression and Anxiety Among People Living With HIV in Bahir Dar, Ethiopia: A Multicenter Study - Tareke, Minale; Belete, Tilahun; Ergetie, Temesgen; Tadesse, Meseret; Menberu, Melak; Ketemaw, Asmamaw (Frontiers in Psychiatry, 2022)
Background: Neurocognitive impairment associated with psychological morbidity such as depression and anxiety among people living with HIV. The presence of these triple burdens affects viral load suppression, treatment adherence, quality of life, treatment outcomes, and functionality. Despite this fact, there is a dearth of studies that examined the triple burden of neurocognitive impairment, co-occurrence of depression and anxiety among antiretroviral therapy attendees in Ethiopia. This study aimed to assess the magnitude of HIV- associated neurocognitive impairment, co-occurring depression and anxiety at the same time among people living with HIV/AIDS Method: Institution-based multi-center cross-sectional study was conducted. A total of 400 were selected using a systematic random sampling technique that has been on antiretroviral therapy follow-up in Bahir Dar City public health institutions. Neurocognitive impairment was assessed using the International HIV Dementia Scale. Besides, co-occurrence of depression and anxiety was assessed using the hospital anxiety and depression scale. A semi-structured questionnaire was applied to collect data on socio-demographic and clinical-related characteristics. Data were analyzed using descriptive statistics, univariate, and multivariable logistic regression. Results: Two-third (66.8%) of people living with HIV had neurocognitive impairment. Co-occurring depression and anxiety in this study was found 39.8%. Being female, having comorbid chronic medical illness and second-line treatment regimen were factors associated with neurocognitive impairment. Furthermore, pill burden, second-line treatment regimen, HIV Clinical stages, social support, HIV-perceived stigma, and neurocognitive impairment were associated factors with co-occurring depression and anxiety. Conclusions: Neurocognitive impairment, co-occurring depression and anxiety were high among people living with HIV/AIDs. Further research is needed to assess the clinical course of neurocognitive impairment and co-occurring depression and anxiety.